HUMAN RELATIONS SEBAGAI KEGIATAN KOMUNIKASI PERSUASIF - Mudzhira Nur Amrullah (Jurnal Komodifikasi, 2015)
Human relation is a persuasive communication held by one to other in face to face and work situation and in a work organization. It aims at stimulating a strong desire to  work enthusiastically based on a productive cooperation. Human relation can also mean a persuasive communication one to another in all situation and all aspect of life that create satisfaction between two sides. In a persuasive communication message delivery done by persuading, ensuring, and enticing etc. until awareness to change emerged voluntarily within communicant without any force.In working situation, leaders conduct an insane and persuasive communication, or in other words as a communicator, leaders send their message ethically and emphatically. In so doing, employments as communicant feel happy to undertake what the leaders wished. Technically, red heering, pay off idea, cognitive dissonance and icing are some technics that can be appied in persuasive communication activities.